Financial culture in business owners and directors: Design and validation of a scale - Robles Acosta, Carlos (RAN - Revista Academia & Negocios, 2025)
Objective: To analyze the metric properties for a scale of financial culture in owners and managers of medium-sized companies in Mexico to facilitate strategic decision making and business sustainability. Method: A Likert-type scale was designed based on the conceptual analysis of the financial culture construct. An expert review and a pilot test were carried out to refine the items. The final sample consisted of 505 subjects. A confirmatory factor analysis was used to evaluate factor loadings, model fit indices and the reliability of the instrument. Results: Confirmatory factor analysis supported an 8-factor model reporting adequate fit indices (NFI=0.91, IFI=0.95, TLI=0.94, CFI=0.95, CMIN/DF= 1.847, SRMR=0.045 and RMSEA=0.041). The estimated factor loadings support the convergent validity of the factors of financial inclusion, self-efficacy and subjective financial knowledge, financial management behaviors, claims anticipation, financial attitude, attitude towards purchase, propensity to indebtedness and compulsive buying. The reliability of the instrument was adequate (?=0.869). Practical implications: The scale is a useful tool for owners and managers of medium-sized companies, allowing them to identify key areas for improving their financial culture. Its application supports their decision-making processes and enhances the financial management of their companies. Originality: It is one of the first specific scales to measure the financial culture of owners and managers of medium-sized companies in Mexico. The scale allows an accurate and contextualized measurement, enabling the development of new research on financial culture, its relationship with other constructs and its evolution over time.